Catalytic Amyloids for Nucleotide Hydrolysis - Castillo-Nara, A; Diaz-Espinoza, R; Escobar-Carrillo, D (Academic Press, 2024)
The design of small peptides that assemble into catalytically active intermolecular structures has proven to be a successful strategy towards developing minimalistic catalysts that exhibit some of the unique functional features of enzymes. Among these, catalytic amyloids have emerged as a fruitful source to unravel many different activities. These assemblies can potentially have broad applications that range from biotechnology to prebiotic chemistry. Although many peptides that assemble into catalytic amyloids have been developed in recent years, the elucidation of convergent mechanistic aspects of the catalysis and the structure/function relationship is still a challenge. Novel catalytic activities are necessary to better address these issues and expand the current repertoire of applicability. In this chapter, we described a methodology to produce catalytic amyloids that are specifically active towards the hydrolysis of phosphoanhydride bonds of nucleotides. The design of potentially active amyloid-prone peptide sequences is explored using as template the active site of enzymes with nucleotidyltransferase activity. The procedures include an approach for sequence design, in vitro aggregation assays, morphological characterization of the amyloid state and a comprehensive methodology to measure activity in vitro using nucleoside and deoxynucleosides triphosphates as model substrates. The proposed strategy can also be implemented to explore different types of activities for the design of future catalytic amyloids. © 2024